PEMBAHARUAN HUKUM PIDANA MENGENAI KETENTUAN PIDANA NARKOTIKA - Yanuar, SH.,L.LM, Fahmi (Kerta Dyatmika, 2015)
ABSTRACTWelfare for every citizen in Indonesia should be guaranteed, whether citizens who are dealing with the law or citizens who are serving a sentence, but in the handling of the offender and drug addicts do not go according to the dicitaka to attain by the Indonesian State, where the case handling narcotics tend actors placed in prison by a state that is still addicted to narcotics, it then makes that the handling of the perpetrators of narcotics placed in custody improper and ineffective and prevent narcotics.In criminal law enforcement needed renewing them in terms of renewal of criminal material, formal criminal law and criminal reform implementation. Updates are run through a set element can be convicted of an act with the concept of the draft new KUHP adhering to the law as the main source of law is the Law, but expands materially formulation of the laws of life in society. Furthermore, in a formal renewal is meperluas with strict accountability and accountability replacement, renewal implementation in criminal, applied Punishment formulated on the purpose of punishment, namely the protection of society and the protection / individual coaching criminals as well as to position the death penalty as a kind of punishment that are exceptional / special. Criminal prosecution against the perpetrators of narcotics and criminal provisions against perpetrators of abuse of these drugs should be prioritized in terms of treatment and care, rather than directly stated punished and placed in LAPAS. The aim is to prevent and combat illicit trafficking, to realize it must first eliminate the effects of dependence that exists within the drug addicts.Â